THE FIRST EXPERIENCE OF TELBIVUDINE THERAPY IN LIVER TRANSPLANT PATIENTS - O. A. Gerasimova; D. A. Granov; F. K. Zherebtsov; V. V. Borovik (Вестник трансплантологии и искусственных органов, 2010)
The first Russian experience of using telbivudine in liver transplant patients discussed in this article. Goal of telbivudine therapy in patients after liver transplantation was a prophylaxis and treatment of chronic hepatitis B recurrence. First data were received after 12 months since start of therapy, viral replication was inhibited, and that was similar with GLOBE trial results published at 2009.